KINERJA PEGAWAI KANTOR CAMAT SEBERIDA KABUPATEN INDRAGIRI HULU - Hilce Presty; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Seberida District Office is a government agency or public organizations in the implementation refers to standardization in the service of showing the duties and functions of each part that is in Head Office Seberida. As a government agency that includes the human resources that employees who work at the institution. Camat Seberida Indragiri Hulu implement development programs work performance of employees. However, if viewed directly in the field then there's also a mismatch with their responsibilities. The work should be completed in a short time could be delayed, employee professionalism in providing services to the community is still poor and own problems that occurred.This study used qualitative research methods to study descriptive data. The concept of using the concept of performance theory. Theory Dwiyanto in Pasolong (2008:203) and Mangkunegara (2010:13). In collecting the data, the researcher used interview, observation, and documentation. By using key informants as a source of information and triangulation techniques for analysis data.These results indicate that the district office employee performance Seberida still not working optimally. Still, there are employees who work not in accordance with its function and follow the vision and mission of the District Seberida. District of Seberida employees also have the ability / level of education that is not in accordance with the job description. Required training for office workers to enhance the performance and capabilities Seberida district office employees to comply with the Mission Vision of the District Seberida.Keyword : Perfomance, Training, Mision Vison